Colistin monotherapy versus colistin-based combination therapy for treatment of bacteremia in burn patients due to carbapenem-resistant gram negative bacteria. Issue 8 (December 2020) - Park, Jin Ju; Seo, Yu Bin; Lee, Jacob; Choi, Young Kyun; Jeon, Jinwoo
Highlights: Colistin-based combination therapy does not improve burn patient clinical outcomes. Eradication rate of CR-GNP was similar for colistin mono- and combination therapy. Mortality rate of burn patients was not improved with colistin combination therapy. Abstract: Carbapenem-resistant gram negative pathogen (CR-GNP) infection in burn patients is a growing concern since treatment options are limited and resistance to the main line of treatment, colistin, is increasing. The goal of this study was to compare treatment outcomes of colistin monotherapy versus colistin-based combination therapy for CR-GNP bacteremia in burn patients. A retrospective observational study was conducted between 2014 and 2017 in Hangang Sacred Heart Hospital located in Seoul, South Korea. Among the burn patients admitted to the burn intensive care unit with CR-GNP bacteremia due to wound infections, colistin monotherapy or colistin-based combination therapy were investigated. We determined both eradication rate within seven days as well as mortality rate within 30 days. A total of 84 burn patients with CR-GNP bacteremia were analyzed—32 were treated with colistin monotherapy and 52 with colistin-based combination therapy. We found that eradication rate within 7 days and 30-day mortality rate were not significantly different between the two groups (71.9% versus 75.0%, P = 0.752 and 31.2% versus 38.5%, P = 0.503). In the Cox regression analysis, Charlson's comorbidity index, renal replacement therapy before colistin use, and duration of antibiotics were associated with 30-day mortality (HR, 1.23; 95% CI, 1.02–1.49; P = 0.030, HR, 2.28; 95% CI, 1.05–4.94; P = 0.037 and HR, 0.94; 95% CI, 0.89–0.99, P = 0.042, respectively). Colistin-based combination therapy did not show significant differences with regard to microbiologic and clinical outcomes compared with colistin monotherapy.